Heterogenous loss of mismatch repair (MMR) protein expression: a challenge for immunohistochemical interpretation and microsatellite instability (MSI) evaluation. (19th December 2018) - McCarthy, Aoife J; Capo‐Chichi, Jose‐Mario; Spence, Tara; Grenier, Sylvie; Stockley, Tracy; Kamel‐Reid, Suzanne; Serra, Stefano; Sabatini, Peter; Chetty, Runjan
Abstract: Immunohistochemistry (IHC) for mismatch repair (MMR) proteins is used to identify MMR status: being diffusely positive (intact/retained nuclear staining) or showing loss of nuclear tumour staining (MMR protein deficient). Four colonic adenocarcinomas and a gastric adenocarcinoma with associated dysplasia that displayed heterogenous IHC staining patterns in at least one of the four MMR proteins were characterised by next‐generation sequencing (NGS). In order to examine a potential molecular mechanism for these staining patterns, the respective areas were macrodissected, analysed for microsatellite instability (MSI) and investigated by NGS and multiplex ligation‐dependent probe amplification (MLPA) analysis of MLH1, MSH2, MSH6 and PMS2 genes, including MLH1 methylation analysis. One colonic adenocarcinoma showed heterogenous MSH6 IHC staining and molecular analysis demonstrated increasing allelic burden of two MSH6 frameshift variants (c.3261delC and c.3261dupC) in areas with MSH6 protein loss compared to areas where MSH6 was retained. Two colonic adenocarcinomas with heterogenous MLH1 staining showed no differences in sequence variants. In one of these cases, however, MLH1 was hypermethylated in the area of MLH1 loss. Another colon carcinoma with heterogenous PMS2 staining (but with retained MSH6) showed both MSH6 c.3261dupC and 3260_3261dupCC where PMS2 protein was lost and only c.3261dupC where PMS2 was retained. The gastric carcinoma showed complete loss of MSH6 in dysplastic foci, while the underlying invasive carcinoma showed retention of MSH6. Both these areas, however, were MSI‐high and showed the same MSH6 variant: c.3261delC. The gastric dysplasia additionally showed MSH6 c.3261dupC. In four of the five cases where MMR protein was lost, these areas were MSI‐high. Heterogenous MMR IHC (focal and/or zonal within the same tumour or between invasive and dysplastic preinvasive areas) is not always due to artefact and is invariably related to MSI‐high status in the areas of loss. An interesting aspect to this study is the presence of MSH6 somatic mutations irrespective of whether MSH6 IHC staining was intact or lost.